2018
DOI: 10.1186/s12985-018-1007-6
|View full text |Cite
|
Sign up to set email alerts
|

Torque teno virus dynamics during the first year of life

Abstract: BackgroundTorque teno virus is a small chronically persisting circular negative ssDNA virus reaching near 100% prevalence. It is reported to be a marker for immune function in immunocompromised patients. The possibility of vertical maternal-fetal transmission remains controversial but incidence rate of TTV DNA in children increased with age. TTV dynamics well studied for allogeneic hematopoietic stem cell transplantation as a predictor of post-transplant complications but there is no viral proliferation kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 25 publications
2
47
0
3
Order By: Relevance
“… 2015 ; Tyschik et al . 2018 ). It is still not clear whether the first infection is symptomatic or not, however, it was shown that TTV and TTMDV genomes are more prevalent in plasma ( P = 0.034) and nasopharyngeal swabs ( P = 0.002) of febrile children compared to afebrile controls (McElvania TeKippe et al .…”
Section: Infection Cycle Of Avs: Genome Replication and Protein Synthmentioning
confidence: 99%
See 1 more Smart Citation
“… 2015 ; Tyschik et al . 2018 ). It is still not clear whether the first infection is symptomatic or not, however, it was shown that TTV and TTMDV genomes are more prevalent in plasma ( P = 0.034) and nasopharyngeal swabs ( P = 0.002) of febrile children compared to afebrile controls (McElvania TeKippe et al .…”
Section: Infection Cycle Of Avs: Genome Replication and Protein Synthmentioning
confidence: 99%
“… 2015 ; Tyschik et al . 2018 ), and that probably most humans are either chronically infected or continuously re-infected, reduces the likelihood that AVs are truly causing disease. One may even consider looking from a completely different perspective.…”
Section: Infection Cycle Of Avs: Genome Replication and Protein Synthmentioning
confidence: 99%
“…www.gastro-j.ru Рос журн гастроэнтерол гепатол колопроктол 2020; 30(4) / Rus J Gastroenterol Hepatol Coloproctol 2020; 30 (4) TTV может быть обнаружен методами количественной или качественной полимеразной цепной реакции (ПЦР) в различных клинических образцах [31][32][33][34]. С этой целью используют стандартную ПЦР, ПЦР со вложенной парой праймеров (nested PCR), ПЦР со вложенным одним праймером (semi-nested PCR) и ПЦР в реальном времени (real-time PCR or RT-PCR) [11,35,36].…”
Section: полимеразная цепная реакция (пцр)unclassified
“…Выявление ДНК TTV в значительной степени зависит от применяемых методов детекции [33,49]. Такие факторы, как тип образца (например, плазма или цельная кровь), различные методы ПЦР или применяемый праймер, могут влиять на выявление ДНК TTV [37,50].…”
Section: распространенность Ttvunclassified
See 1 more Smart Citation